Islamic Financial Instruments and the Dynamics of the Islamic Stock Exchange - Ratna, Ai (Islamicate Institute, 2019)
This study investigates the structuring and implementation of Islamic financial instruments within stock exchanges, emphasizing their alignment with sharia principles and evaluating their practical challenges. Drawing on Islamic jurisprudence and modern finance theory, the research applies a qualitative-descriptive method supported by document analysis. Findings indicate that Islamic instruments—such as sukuk, mudharabah, and musharakah—are grounded in ethical, risk-sharing, and asset-backed principles. However, operational and regulatory issues, including fragmented compliance standards, limited liquidity, and investor literacy gaps, hinder their full effectiveness. The study also identifies key strategies to improve the sustainability of Islamic stock exchanges, including regulatory harmonization, technological innovation, and capacity-building initiatives. The research contributes theoretically by bridging Islamic legal frameworks with institutional finance models and practically by offering policy recommendations. These insights affirm that Islamic stock exchanges can serve as ethical and competitive alternatives in global capital markets when adequately supported by institutional reform and public engagement.